3D-printed concrete with recycled glass: Effect of glass gradation on flexural strength and microstructure. (3rd January 2022) - Liu, Junli; Li, Shuai; Gunasekara, Chamila; Fox, Kate; Tran, Phuong
Highlights: Different gradations of recycled glass replaced river sand in 3D-printed concrete. Porosity and fracture surface were investigated by X-ray micro-computed tomography. Glass particle inclusions have opposite effects on flexural properties in different loading directions. Adding different gradations of glass evidently affects the porosity and pore morphology. Recycled glass with different sizes demonstrated the influences on the way crack propagates. Abstract: The interest in sustainable 3D concrete printing (3DCP) has been growing in recent years. One pathway to promoting sustainable 3DCP is replacing natural river sand with recycled glass. Previous research has focused on the rheological and mechanical properties of 3D-printed concrete with recycled glass. However, the correlation between mechanical properties and microstructures were rarely reported. This study investigated the flexural properties of 3D-printed concrete with 50% sand replaced by different gradations of recycled glass through three-point bending tests. The mid-point load for the bending test was constantly along the direction of layer deposition during 3D printing. Two test conditions were designed, including the beam span parallel and perpendicular to the printing direction, respectively. Microstructural investigations on specimens were carried out through X-ray micro-computed tomography (µCT) and scanning electron microscopy (SEM). Experiment results showed the reference mixture without glass exhibited brittle fracture, in contrast to those with glass showing strain softening in the post-peak region. When specimen span was parallel to printing direction, the addition of glass decreased flexural strength by 8% to 20%. µCT analysis showed the crack propagation was primarily conditioned by the contents and morphology of pores correlated to the addition of glass. However, the addition of glass particles increased flexural strength by 25% to 33% when the beam span was perpendicular to the printing direction. Based on µCT and SEM analysis, the strength improvement and crack development in this condition was primarily related to the glass particles located alongside the crack path.